2020
DOI: 10.1007/s13167-020-00228-9
|View full text |Cite
|
Sign up to set email alerts
|

Intestinal alkaline phosphatase modulation by food components: predictive, preventive, and personalized strategies for novel treatment options in chronic kidney disease

Abstract: Alkaline phosphatase (AP) is a ubiquitous membrane-bound glycoprotein that catalyzes phosphate monoesters' hydrolysis from organic compounds, an essential process in cell signaling. Four AP isozymes have been described in humans, placental AP, germ cell AP, tissue nonspecific AP, and intestinal AP (IAP). IAP plays a crucial role in gut microbial homeostasis, nutrient uptake, and local and systemic inflammation, and its dysfunction is associated with persistent inflammatory disorders. AP is a strong predictor o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 140 publications
0
13
0
Order By: Relevance
“…Chronic inflammation is a hallmark of the majority of non-communicable diseases (cancer, degenerative disease, autoimmune disease, etc.) [18][19][20] and is harmful. Inflammation can promote the occurrence and development of cancer by various ways (blood vessel growth, proliferation and invasiveness, et c.), which indicated that monitoring of the causes and inflammatory factors in chronic inflammation processes is a useful way to predict cancer and assess the efficiency of cancer prevention [17,21].…”
Section: Molecular Mechanisms Of Inflammation In Glaucomamentioning
confidence: 99%
“…Chronic inflammation is a hallmark of the majority of non-communicable diseases (cancer, degenerative disease, autoimmune disease, etc.) [18][19][20] and is harmful. Inflammation can promote the occurrence and development of cancer by various ways (blood vessel growth, proliferation and invasiveness, et c.), which indicated that monitoring of the causes and inflammatory factors in chronic inflammation processes is a useful way to predict cancer and assess the efficiency of cancer prevention [17,21].…”
Section: Molecular Mechanisms Of Inflammation In Glaucomamentioning
confidence: 99%
“…ESRD patients are more susceptible to periodontal disease due to general debilitation and depression of the immunological system. The altered saliva composition and persistent low-grade inflammation in patients with CKD also mechanistically influence the onset and/or progression of periodontal disease [ 8 , 9 ]. In the progression of CKD, more cytokines were secreted by inflammatory cells to the inflammation sites, which aggravates the periodontal disease [ 10 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…The postmenopausal group showed an increase in alkaline phosphatase (ALP) compared to the premenopausal group. This increase, even within reference values, has been correlated with age-related diseases such as cardiovascular and inflammatory diseases [ 34 , 35 ], but it should be noted that other conditions that also elevate ALP, such as biliary obstruction, hepatitis, renal failure, severe anemia, and bone disorders such as osteoporosis, were not investigated in this cohort, which may limit our findings.…”
Section: Discussionmentioning
confidence: 75%